2015
DOI: 10.1186/s12906-015-0974-z
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Rhei Rhizoma on reflux esophagitis in rats via Nrf2-mediated inhibition of NF-κB signaling pathway

Abstract: BackgroundRhei Rhizoma has been widely used as a traditional herbal medicine to treat various inflammatory diseases. The present study was conducted to evaluate its anti-inflammatory activity against experimental reflux-induced esophagitis (RE) in SD rats.MethodsRhei Rhizoma was administered at 125 or 250 mg/kg body weight per day for 7 days prior to the induction of reflux esophagitis, and its effect was compared with RE control and normal rats.ResultsRhei Rhizoma administration markedly ameliorated mucosal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Images were acquired with a digital camera to calculate the ratio of esophageal damage using Image J software. Esophageal lesion index were calculated following: esophageal lesion index (%) = [esophageal damage area (mm 2 )/ esophagus total area (mm 2 )] × 100 (Kwon et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Images were acquired with a digital camera to calculate the ratio of esophageal damage using Image J software. Esophageal lesion index were calculated following: esophageal lesion index (%) = [esophageal damage area (mm 2 )/ esophagus total area (mm 2 )] × 100 (Kwon et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have reported the protective effect of plant extract on rat esophageal tissue damage caused by gastric acid reflux. For example, Rhei Rhizoma protected rat RE by its anti‐inflammatory effect in vivo (Kwon et al, 2016), and Artemisia campestris extract and chlorogenic acid protected esophageal mucosa injuries induced by gastric content reflux through its antioxidant properties (Jabri, Tounsi, Abdellaoui, Marzouki, & Sebai, 2018; Kang & Lee, 2014). However, the study of possible molecular mechanism of RE is imperfect.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluated protective effects of geraniin on reflux esophagitis rats, experimental rats were orally administrated with geraniin (15 and 30 mg/kg body weight) and ranitidine 30 mg/kg body weight 90 min before the surgery. Then, the rats except for those in the normal control group, were subjected to laparotomies to ligate the pylorus and the junction between the forestomach and the corpus [17], and esophageal damage was induced by gastric acid reflux during the ligation. Our data showed that the esophageal tissue of the RE control group showed tissue damages and hemorrhage induced by inflammation compared to the normal control group (Fig.…”
Section: Changes Of Esophagus Tissue Damage In Acute Re Ratsmentioning
confidence: 99%
“…By ligating the pylorus to prevent gastric contents from entering the duodenum and by ligating the forestomach to reduce stomach volume, gastric acid is more likely to re ux into the esophagus [32]. Gastric acid re ux leads to esophageal damage including in ammatory in ltration of esophageal cells and shedding of mucosal epithelial tissue [33]. In addition, the expression levels of in ammatory proteins and pro-in ammatory factors in the esophageal tissue vary depending on degree of esophageal injury and in ammation [34].…”
Section: Discussionmentioning
confidence: 99%